Kontruksi Filosofis Perlindungan Hak Asasi Manusia Minoritas Keagamaan dalam Konstitusi Indonesia - Fatwa, A. Fajruddin (al-Daulah: Jurnal Hukum dan Perundangan Islam, 2014)
Abstract: This article focuses on presenting problem of religious minority right in Indonesia. Based on its constitution, Indonesia has equal protection for all citizens. There are some basic religion right clearly protected and presented in constitutional and criminal law. Unfortunately, violation of minority rights still continues in Indonesian life. According to research data, there are a big gap perception between government and the people. Government choose to float the norms of religious minority right protection in abstract level and most of religious minority group asked more detail and concrete norm.Keywords: Religious minority protection, human rights, religious minority.